Changing Europe : identities, nations and citizens - Dunkerley, David (Routledge, 2003)
Introduction to issues shaping new Europe and its citizens, such as the idea of 'Europe', development of the nation state, European identity and challenges posed by citizenship, migration, human rights, regionalism and nationalism.